Framework for Kidney Health Follow‐Up Among Neonates With Critical Cardiac Disease: A Report From the Neonatal Kidney Health Consensus Workshop - Gorga, Stephen M.; Beck, Tara; Chaudhry, Paulomi; DeFreitas, Marissa J.; Fuhrman, Dana Y.; Joseph, Catherine; Krawczeski, Catherine D.; Kwiatkowski, David M.; Starr, Michelle C.; Harer, Matthew W.; Charlton, Jennifer R.; Askenazi, David J.; et al. (Journal of the American Heart Association, 2025)
Acute kidney injury is common among neonates with critical cardiac disease. Risk factors and associations with kidney‐related outcomes are heterogeneous and distinct from other neonates. As survival of children with critical cardiac disease increases to adulthood, the burden of chronic kidney disease is increasing. Thirty percent to 50% of adults with congenital heart disease have impaired kidney function, even in the absence of prior kidney injury episodes. This may be related to the current standardized acute kidney injury criteria, which may not fully capture clinically meaningful kidney injury and long‐term kidney health risks. An improved understanding of which neonates with critical cardiac disease should undergo kidney health follow‐up is imperative. During the National Institutes of Health–supported Neonatal Kidney Health Consensus Workshop to Address Kidney Health meeting conducted in February 2024, a panel of 51 neonatal nephrology experts focused on at‐risk groups: (1) preterm infants, (2) critically ill infants with acute kidney injury, and (3) infants with critical cardiac disease. The critical cardiac disease subgroup, comprising multidisciplinary experts, used a modified Delphi process to achieve consensus on recommendations for kidney health follow‐up. In this report, we review available data on kidney health follow‐up in critical cardiac disease and summarize the 2 consensus‐based recommendations. We introduce novel diagnostic and risk‐stratification tools for acute kidney injury diagnosis in neonates with cardiac disease to guide follow‐up recommendations. Finally, we identify important knowledge gaps, representing areas of focus for future research. These should be prioritized to understand and improve long‐term kidney health in critical cardiac disease.